Inovasi Interactive Virtual Tour Platform dalam Meningkatkan Ecotourism di Taman Wisata Harmony, Surabaya Dengan Pendekatan Design Thinking - Rendra Suprobo Aji; Tri Budi Santoso; Kholid Fathoni; Sritrusta Sukaridhoto; Muhammad Agus Zainuddin; Widi Sarinastiti; Ashafidz Fauzan Dianta; Zakha Maisat Eka Darmawan; Hestiasari Rante; Rosiyah Faradisa; Moh. Zikky; Irma Wulandari; Akhmad Alimudin (Pusat Publikasi ITS, 2026)
This research explores the development and effectiveness of an interactive web-based virtual tour application using 360-degree videos as an innovation to enhance ecotourism at the Taman Wisata Edukasi, Surabaya. The development of this virtual tour platform employs a Design Thinking approach, which focuses on the platform design process based on user needs and the creative process in its development. The result is a virtual tour platform that provides a realistic experience, explores the Harmony Garden thematically, and presents an ambiance that can attract web visitors and encourage them to visit the location. The development of this virtual tour video becomes an attractive feature, positioning the Harmony Garden as a thematic park worth visiting.